An annotated checklist of birds of the Vilanculos Coastal Wildlife Sanctuary, Southern Mozambique - Read, Christine; Tarboton, Warwick R; Davies, Gregory BP; Anderson, Mark D; Anderson, Tania A (Biodiversity Observations, 2014)
It is possible that episodic recharging of wetlands by tropical cyclones is an important and overlooked ecological factor in creating suitable habitat for breeding waterbirds in Mozambique.